P205 Why do radiologists under-report pulmonary TB on chest X-rays in south london?. (12th November 2019) - Kamalanathan, M; Benedetti, G; Azam, A; Breen, R
Abstract : Introduction: Delays in diagnosis of pulmonary tuberculosis (TB) are common. Although slow referral for a chest x-ray (CXR) can contribute to diagnostic delay, we previously reported that only half of patients with active pulmonary TB and an abnormal CXR had their CXR reported as possible TB. 1 In most cases the CXR showed what appeared to the TB team as easily recognisable features of infection, and so we sought to identify possible reasons for under-reporting from the perspective of the radiologists. Objectives: To evaluate the experience and training of radiologists at a London teaching hospital in reporting pulmonary TB on a CXR. Methods: We invited all radiologists from ST1 to Consultant level who report CXR to complete an online survey. Responses were collected from January – April 2019 and were anonymous. Results: 33 of 60 (55%) radiologists responded to the survey: 12 consultants and 21 trainees ranging from ST1 to ST5. 79% (26/33) had previously reported a CXR as TB or included it in the list of differentials. 58% (17/33) were neutral to not at all confident in reporting TB from a CXR (figure 1). 9% (3/33) had considered TB as the diagnosis but not included it in the report. 40% (13/33) had never had specific teaching about TB radiology, and 79% (26/33) thought that further teaching would help with their reporting. 79% (26/33) said that they were not aware of local TB referral pathways or what would happen to the patient if they mentioned TB. Following this survey we invited all radiologists to a teaching session with the TB team. Conclusions: Our data suggests that despite working in hospitals with a significant burden of TB, more than half of radiologists lacked confidence in including TB in the CXR report. We have identified the need for increased education and training in TB radiology and ensuring that reporting radiologists of all grades are aware of local rapid referral pathways for TB. This is essential to increase early diagnosis of TB and reduce delays in treatment initiation. Reference: Myall K, et al . P166|Diagnosing Pulmonary Tuberculosis: How useful is the chest x-ray report? Thorax 2017;72:A173.